2017
DOI: 10.3945/cdn.117.000919
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment of Overweight and Obesity with Polyglucosamine (PG L112): Randomized Study Compared with Placebo in Subjects after Caloric Restriction

Abstract: Background: Short-term treatment of overweight and obesity with polyglucosamine (PG) was found to be more effective than placebo and orlistat in double-blind clinical studies. Objective: The aim of the study was to compare the efficacy of long-term (12-mo) treatment of weight loss with PG and placebo (PL). Methods: This was a double-blind randomized study in 100 participants of both sexes with a body mass index (in kg/m2) >30 to <35. One group of 50 participants was treated for 1 y with PG at 1.6 g/d and a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…The data of the present study are a confirmation of what has been described in children suffering from Down syndrome and OSA [10], who were having clinical benefit increasing the oral wettability and hygiene.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The data of the present study are a confirmation of what has been described in children suffering from Down syndrome and OSA [10], who were having clinical benefit increasing the oral wettability and hygiene.…”
Section: Discussionsupporting
confidence: 79%
“…Patients had to be familiar with the Food Intake Questionnaire [10] because they were part of the screening program for the asymptomatic vascular disease [14] using FIA (for food intake control) and following a SM. in only, whereas at baseline and after 4 weeks of treatment values were taken only in the last day of the week.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several clinical trials have investigated the effects of polyglucosamines on weight loss in subjects with overweight and obesity [9,11,12,[14][15][16]. A few of these studies demonstrated significant reductions in body weight, whereas others were inconclusive.…”
Section: Introductionmentioning
confidence: 99%